GENDER RELATIONS IN STEINBECK'S - THE GRAPES OF WRATH - DIAS, Daise Lílian Fonseca (2005)
The objective of this paper is to analyze gender relations in mutation in Steinbecks masterpiece The grapes of wrath from a feminist perspective. A detailed analysis will be made of the way the author portrays women and gives decisive roles to them, while the figure of the male provider collapses in a chaotic universe of economic depression - breaking the apparent misogynist pattern he followed in his early fiction.